Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T19:19:35+01:00
4(2x+3) - 2(4y-1)=30
8x+12-8y+2=30
8x-8y=30-14
8x-8y=16

5x+1/3 -y- 3/4=3 /* 12(wspólny mianownik dla 3 i 4)
60x +4-12y -9=36
60x - 12y=36-4+9
60x-12y=38
2009-12-07T19:24:01+01:00
4(2x+3)-2(4y-1)=30
5x+1/3-y-3/4=3

8x+12-8y+2 =30
5x+1=9-3y-9/4

8x-8y=16 |x3
5x+3y=5 i 3/4 |x8

24x-24y=48
40x+24y=46

64x=94
x=94/64

16- 8 *(94/64) = -8y
-8y= 11 i 3/4

y=-94 x= 94/64
2009-12-07T19:42:58+01:00
A)

8x+12-8y+2=30
8x-8y+14-30=0
8x-8y-16=0
Δ=8²-4*8*(-16)
Δ=64+512
Δ=(pierwiastek) 576= 34
x₁=8-24/ 16
x₁=(-1)

x₂=8+24/ 16
x₂=2


b)
5x+1/3 - y - 3/4 = 3 /*12
60x+4-12y-9-3=0
60x-12y-16=0 /4
15x-3y-4=0
Δ=9+240=15,8

x₁=9-(pierw z 15,8 /30
x₁= 3- pier 15,8 / 10

x₂=3+pierw z 15,8 / 10